ANALISIS PANDANGAN ORGANISASI ANTI-ISLAM TERHADAP EKSISTENSI IMIGRAN MUSLIM DI JERMAN - Ismi Nurhaidah (WANUA : Jurnal Hubungan Internasional, 2017)
This study aims to find out how the views of anti-Islamic organizations on the existence of Muslim immigrants in Germany. Germany is one of the main destinations of immigrants from the Middle East. Germany is one of the most hospitable countries in accepting immigrants.This is because there is more attention to refugees that can be seen in foreign policy initiated by German Chancellor Angela Merkel. Even as the waves of immigrants grew, Germany continued to open the door for their arrival. The arrival of Muslim immigrants in Germany, which has been increasing annually, has led to various refusals from conservatives and anti-Islamic organizations. They assume the presence of Muslim immigrants will cause social problems. They also oppose to an integration effort between immigrant and German societies because there is a fear that the effort will diminish the original identity of the Europeans. This type of research is descriptive-explanatory where researchers aim to describe the views of anti-Islamic organizations to the presence of Muslim immigrants demonstrated through efforts in the conduct of Islamophobia in Germany.Analysis of the research problem using constructivism theory and the concept of Islamophobia. The researchers will explain the organizational outlook based on constructivism perspective to analyze the cause of the development of Islamophobia in Germany. Constructivism will explain why a framework of thought within the organization exists. This theory is also used to strengthen the foundation of the researcher's thinking in looking at one of the phenomena of globalization that occurs today.